Developmental Ecological Psychology: Changes in Organism-Environment Systems Over Time, Part II. Issue 2 (3rd April 2018) - Read, Catherine; Szokolszky, Agnes
ABSTRACT: As invited editors of this 2-part Special Issue, we ended the Introduction to Part I of this Special Issue (Read & Szokolszky, 2018 ) with a claim that the Ecological Psychology revolution would not be complete without Developmental Ecological Psychology. The inclusion of developmental work requires considering some basic questions regarding change in organism-environment systems over time and of how to describe and study such changes over stretches of time. J. J. Gibson (1966, p. 321) ended with a dedication to "all persons who want to look for themselves." We dedicate this 2-part Special Issue to all persons who want to look for themselves over time .